Platelet-Rich fibrin (PRF) and its application in dentistry: A literature review - Poulami Goswami; Vivek Chaudhary; Ashtha Arya; Richa Verma; Gopikrishnan Vijayakumar; Mallanna Bhavani (Wolters Kluwer Medknow Publications, 2024)
Platelet-rich fibrin (PRF) is a biocompatible fibrin matrix that acts as a resorbable membrane, collecting platelet cytokines, growth factors, and cells and releasing them. It is easily extracted from blood. Many dentists use PRF, a concentrated growth factor solution, to treat various lesions and regenerate tooth and oral tissues. This research examines the pros, cons, and suggestions of using PRF in dentistry.